Practice of Academic Guidance at High School Level: A Longitudinal Case Study - ÖKSÜZOĞLU, Meryem (Journal of Research in Educational Sciences, 2016)
This paper investigates the academic guidance and counseling services provided in North Cyprus to ninth grade students (first year of high school) since 2005-2006 academic year. The extent of its efficiency is investigated through student and teacher perspective of the largest regular public high school and the largest vocational public high school in Nicosia, North Cyprus. Data were collected in 2005 and 2015 to compare the reality and their responses after ten years. From the regular public high school, four counseling and guidance teacher; and eight students; and from the vocational public high school, four counseling and guidance teacher and eight students participated. The data were collected by semi-structured interviews. Participant teachers and students were asked questions about guidance practices within their schools and their perception. The findings suggest that, guidance services were not as efficient as expected with the new restructuration policies and that rooted in the fact that students’ talents and interests could not be efficiently analyzed and directed. This inefficiency was due to the problems arising as a result of the impediments of the system itself. Another detail was the lack of guidance practices as late as the first year of high school.
Keywords: Academic Guidance; High School; North Cyprus